(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Beyond the limited number of cases in which we have at our disposal native language epigraphy, the information (usually difficult to interpret) that the proper names known to us thanks to Greek and Roman sources can provide is, no doubt, potentially of great value. Besides the most abundant and best studied names, personal names, we have got divine names, place names and, finally, ethnic names, that is, the names with which our sources denominate the groups that they perceive as ethnic entibies of a minimum coherence. This paper undertakes a study of the main ethnonyms that we know from Ancient Hispania, in a total of 54 entries, with the main intention of making use of the linguistic information contained in them in order to obtain certain conclusions relative to the dispersión of different languages throughout the Peninsula. The ethnic names from Ancient Hispania constitute a group of proper names of great interest, to which, not enough attention has been given so far. In comparison with place names, it is reasonable to think that, in an important number of cases, ethnic names are probably closer, in chronological terms, to the language of the people using them.